(untitled) (Bangladesh Journal of Infectious Diseases, 2022)
Globally, millions of documented SARS-CoV-2 infections with hundreds of thousands of deaths already reported. The majority of the fatal events have been reported in adults older than 70 years and those who have multiple co-morbidities. Despite the misery fatality of the virus, a significant number of peoples recovered from critical conditions also. Mild cases improved significantly with symptomatic management with strict maintenance of isolation. Therefore, many people believed that COVID-19 is a short-term illness, mild cases recovered completely within 2 weeks and severe or critical illness may require 3-6 weeks for complete recovery. However, the latest issue coming forward is delayed recovery in the surviving patients from severe or moderate COVID presenting with multisystem complications. We reported two cases of post COVID complications, newly named as “long COVID syndrome”. We described the common symptoms two patients experienced following recovery from acute phase of COVID-19 and how they were managed. We also discussed on the pathogenesis and management plan of common symptoms persisting after recovery of COVID-19. Bangladesh Journal of Infectious Diseases 2021;8(1): 42-49